História da ciência no ensino de física: uma proposta de sequência de ensino investigativo e seu desdobramento no contexto do currículo paulista - Oliveira, Nathália Andrade Candido de (Universidade Federal de São Carlos, 2024)
The central theme of this research is the study of the History of Science in the Teaching of Physics, specifically focusing on optics. From this perspective, we discuss and analyze the curriculum guidelines of the state of São Paulo, aiming to observe their implications for teaching. Consequently, the main objective of the dissertation is to study the History of Science in Physics Education, and as a result, it proposes an Investigative Teaching Sequence (ITS) for the topic of optics. This ITS aims to highlight its developments in relation to the São Paulo Curriculum guidelines, as well as to enhance understanding of aspects related to the Nature of Science. This qualitative research primarily analyzes the Investigative Teaching Sequence in two aspects: its feasibility within the São Paulo Curriculum and the assumptions and conceptual understanding concerning the Nature of Science. Among the findings, we can highlight that the proposed ITS aligns well with the Skills, Competencies, and knowledge objects stated by the São Paulo Curriculum. Furthermore, the ITS adopts a didactic approach that focuses on investigative teaching and develops the History of Science for the Teaching of Optics both coherently and thoroughly. These aspects were identified as gaps in the existing literature and in the São Paulo Curriculum itself. It is important to note that the curriculum, as it is currently structured, tends to diminish the disciplinary specificity and reduce the class time allocated to the physics curriculum component. This could result in less autonomous teaching and restrict students' access to certain content. Moreover, the developed ITS aligns with a proper understanding of the aspects related to the Nature of Science, aiming to minimize distorted views on the subject. In conclusion, the research seeks to contribute to the teaching profession, particularly for professionals working within the São Paulo State Department of Education. It also aims to enhance the provision of quality basic education by promoting aspects of teaching and learning in physics, based on the discussions presented here.
Science history in physics education: a proposal for an investigative teaching sequence and its developments within the são paulo curriculum context
Keywords: História da ciência; Sequência de ensino investigativo; Currículo paulista; Natureza da ciência; History of science; Investigative teaching sequence; São Paulo state curriculum; Nature of science; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM